2019
DOI: 10.1111/aab.12513
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence analysis of phytoplasma strains of 16SrII group in Iran and their comparison with related strains

Abstract: Phytoplasmas of the group 16SrII (peanut witches'-broom group) are among the most important phytoplasmas identified in Iran. These phytoplasmas are so diverse that they have been classified within 23 subgroups, among which phytoplasmas of subgroups 16SrII-B, -C and -D have been recognised in Iran. In this study, we used multilocus sequence analysis as a tool to find the extent of genetic diversity and phylogeny of representative phytoplasmas of 16SrII in Iran in comparison to reference phytoplasma strains char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…The results further confirmed the validity and utility of these four genes as additional molecular markers for characterization of phytoplasma strains belonging to 16SrI-B and 16SrII-D subgroups. Multilocus genes have been successfully used earlier for finer differentiation of closely related subgroup phytoplasmas strains (Martini et al 2007 ; Bohunická et al 2018 ; Siampour et al 2019 ). However, in the present study, all the four genes used provided similar results of grouping and subgrouping classification of rose balsam phytoplasma strains indicating that the rose balsam phytoplasma strains identified from two states of India do not have significant genetic diversity among themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The results further confirmed the validity and utility of these four genes as additional molecular markers for characterization of phytoplasma strains belonging to 16SrI-B and 16SrII-D subgroups. Multilocus genes have been successfully used earlier for finer differentiation of closely related subgroup phytoplasmas strains (Martini et al 2007 ; Bohunická et al 2018 ; Siampour et al 2019 ). However, in the present study, all the four genes used provided similar results of grouping and subgrouping classification of rose balsam phytoplasma strains indicating that the rose balsam phytoplasma strains identified from two states of India do not have significant genetic diversity among themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study confirmed the suitability of imp gene in fine differentiation of closely related phytoplasmas within the group 16SrIX. Similarly, imp gene has been used in several studies as a genetic marker for differentiation of closely related phytoplasmas (Bohunická et al, 2018; Siampour, Izadpanah, Martini, & Salehi, 2019). The topology of the imp ‐based phylogenetic tree was comparable to that depicted based on conserved rp gene.…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA extracted from two periwinkle plants infected by cucumber phyllody phytoplasma (CuPh, 16SrII‐D; GenBank accession no. KY412986) were also utilised as positive controls in PCR assays (Siampour, Izadpanah, Martini, & Salehi, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aurantifolia' or 'Ca. P. australasiae' (Siampour et al, 2019), although the latter species has not been further supported (IRPCM, 2004). Phytoplasma infecting S. tuberosum are categorised here, and they include 'GD32 (Cheng et al, 2019), St_JO_10, 14, 17 (Salem et al, 2019), PPT-SA (Omar et al, 2018), Rus-343F (Girsova et al, 2016), PPT-GTO29, PPT-GTO30, PPT-SINTV (Santos-Cervantes et al, 2010), Potato Huayao Survey 2 (Hodgetts et al, 2009), Potato hair sprouts, PHS (Leyva-Lopez et al, 2002).…”
Section: Pest Categorisation Of Non-eu Potato Phytoplasmasmentioning
confidence: 99%